2018
DOI: 10.5812/ijcm.82926
|View full text |Cite
|
Sign up to set email alerts
|

BMI1 Roles in Cancer Stem Cells and Its Association with MicroRNAs Dysregulation in Cancer: Emphasis on Colorectal Cancer

Abstract: Context: Colorectal cancer (CRC) is among the most common cancers in the world. Despite the existence of different treatment strategies such as chemoradiation and surgery, CRC therapy still remains a significant challenge as a result of the existence of cancer stem cells (CSCs). Evidence Acquisition: This review is comprised of research and review studies published in valid databases such as PubMed, Sci-enceDirect, Medline, Google Scholar, and Scopus, using the following keywords: BMI1, cancer stem cell, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…In silico analysis and in vitro selection revealed that miR-1291 was an upstream modulator of DCLK1. miR-1291 also decreased the expression of CSC markers BMI1 and CD133, but scarcely decreased CD166 expression (25,26,68,74). Since these molecules are not likely to be direct targets of miR-1291 according to TargetScan predictions, it is postulated that the decrease in BMI1 and CD133 may reflect certain diminution of the stem-like properties of HCT116 cells, which could be an indirect effect of miR-1291 through DCLK1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico analysis and in vitro selection revealed that miR-1291 was an upstream modulator of DCLK1. miR-1291 also decreased the expression of CSC markers BMI1 and CD133, but scarcely decreased CD166 expression (25,26,68,74). Since these molecules are not likely to be direct targets of miR-1291 according to TargetScan predictions, it is postulated that the decrease in BMI1 and CD133 may reflect certain diminution of the stem-like properties of HCT116 cells, which could be an indirect effect of miR-1291 through DCLK1.…”
Section: Discussionmentioning
confidence: 99%
“…CSCs confer resistance to anticancer drugs and radiotherapy, and thus cause distant metastases and recurrence ( 22 - 24 ). Several CSC markers for CRC have been identified, including CD133, B cell-specific Moloney murine leukemia virus integration site 1 (BMI1) and leucine rich repeat containing G protein-coupled receptor 5 ( 23 , 25 , 26 ). Previously, doublecortin-like kinase 1 (DCLK1) was demonstrated to be a CSC marker in CRC ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…miR-125b and miR-128, two of the major miRNAs described to be downregulated in GBM, show a remarkably lower expression in CD133+ GSCs, as compared with CD133-cell populations. Upon expression, they both inhibit GBM growth by decreasing the self-renewal and proliferation of GSCs, via BMI1 Proto-Oncogene, Polycomb Ring Finger (BMI-1) downregulation, thereby exerting a pro-apoptotic role [65,66,67,68,69,70,71]. Moreover, miR-128 represses GSCs growth and mediates their differentiation by targeting the oncogenic EGFR/Platelet-Derived Growth Factor Receptor/AKT Serine/Threonine Kinase (EGFR/PDGFR/AKT) signaling [68,72,73].…”
Section: Mirnas In Human Neural Cscsmentioning
confidence: 99%
“…BMI‐1 is involved in different pathways, including axial patterning, hematopoiesis, cell cycle regulation, and senescence [13]. Furthermore, besides its roles during development, BMI‐1 expression faces alterations in different cancer types, including CRC and then could be considered as an oncogene [14, 15].…”
Section: Introductionmentioning
confidence: 99%